Diversity of Butterfly Types (Lepidoptera: Rhopalocera) Based on Altitude Variations in Sibayak II Forest, North Sumatra - Aditya, Wahyu; Hutasuhut, Melfa Aisyah; Tambunan, Efrida Prima Sari (Jurnal Biologi Tropis, 2024)
Butterflies belong to the order Lepidoptera which has essential roles such as pollinating insects (pollinators), evaluating environmental quality, and indicators of habitat change. The research aims to determine the types of butterflies, diversity, relative abundance, and dominance index in the Sibayak II Forest area of North Sumatra. This research is a quantitative descriptive research by combining the cruising method and the VES method. Sampling was carried out at three altitudes 1300-1500 masl, 1500-1700 masl, and 1700-1900 masl using insect nets. The results obtained were 31 species of butterflies from 6 families, with the highest number of individuals from three heights, namely Mycalesispatiana in Sibayak II Forest, North Sumatra. The index value of butterfly species diversity in Sibayak  II Forest with an average value of 2.67 is included in the medium category. The relative abundance index value of the most abundant butterfly species is the Mycalesis patiana with a discount of 34%. The overall butterfly dominance index value is 0.124. Based on the species diversity index, relative abundance and dominance index indicate environmental conditions in accordance with the life cycle and food sources as well as the distribution of host plants in Sibayak  II Forest.